(De)constructing organizational boundaries of university administrations: changing profiles of administrative leadership at German universities. Issue 2 (2nd April 2016) - Blümel, Albrecht
ABSTRACT: By analysing institutional changes of administrative leadership at German universities, this paper studies the construction of organizational boundaries as an important aspect of organizational transformation of universities as complete organizations. Building on an analysis of the formal status of administrative leadership at universities derived from higher education laws in Germany and occupational profiles of heads of university administrations based on a content-analysis of curriculum vitaes ( N  = 298), this paper seeks to contribute to a neglected domain in higher education research. It is argued that alterations to the formal status of administrative leaders from an ambivalent position between the ministry and the university to an integrated member of the university leadership can be seen as the embodiment of the construction of organizational boundaries vis-à-vis the state, whilst at the same time dissolving internal boundaries with regard to the former separation between academic and administrative affairs. By the same token, the formerly closed occupational group of heads of university administrations as law-educated members of the civil service has been opened to form a more heterogeneous composition of administrative leadership.